American Economic Association Committee on Statistics (AEAStat): Annual Report—2010 - Shapiro, Matthew D (American Economic Review, 2011)
The current members of the Committee on Economic Statistics are Matthew Shapiro, University of Michigan (Chair); Mark Bils, University of Rochester; Dennis Fixler, Bureau of Economic Analysis; Barbara Fraumeni, University of Southern Maine; David Johnson, Census Bureau; Randall Kroszner, University of Chicago; Jonathan Parker, Northwestern University; Charles Schultze, Brookings Institution; and Jack Triplett. In January 2007, the Executive Committee voted to give the Committee standing authority to organize three sessions each year for inclusion on the program of the Association’s annual meeting. At its April 2008 meeting, the Executive Committee voted to allow the Committee to designate one session each year for publication in the annual Papers and Proceedings volume. For the January 2011 meeting, the Committee circulated a call for papers related to the statistical issues arising from the financial crisis and potential changes in financial regulations, markets, and institutions in addition to any topics related to economic statistics. The following three sessions are included in the program of the January 2010 meeting: “Frontiers of Productivity and Output Measurement,” “New Approaches to Measuring Household-Level Finances,” and “Measuring Financial Capacity and Risk: Lessons from the Financial Crisis.” Details of the sessions are given in the Table. The Committee has also undertaken the task of commissioning reviews of needs for data in particular subject matter areas. A group cochaired by Robert Feenstra and Robert Lipsey completed a report on data needs for research on international trade. It was discussed at this year’s National Bureau of Economic Research Summer Institute meetings. It is scheduled for discussion at a meeting of the Federal Economic American Economic Association Committee on Statistics (AEAStat)